Discovery of a 12 billion solar mass black hole at redshift 6.3 and its challenge to the black hole/galaxy coevolution at cosmic dawn. Issue Volume 11:Issue S319(2015) (17th August 2016) - Wu, Xue-Bing; Wang, Feige; Fan, Xiaohui; Yi, Weimin; Zuo, Wenwen; Bian, Fuyan; Jiang, Linhua; McGreer, Ian D.; Wang, Ran; Yang, Jinyi; Yang, Qian; Thompson, David; et al.
Abstract: The existence of black holes with masses of about one billion solar masses in quasars at redshifts z > 6 presents significant challenges to theories of the formation and growth of black holes and the black hole/galaxy co-evolution in the early Universe. Here we report a recent discovery of an ultra-luminous quasar at redshift z = 6.30, which has an observed optical and near-infrared luminosity a few times greater than those of previously known z > 6 quasars. With near-infrared spectroscopy, we obtain a black hole mass of about 12 billion solar masses, which is well consistent with the mass derived by assuming an Eddington-limited accretion. This ultra-luminous quasar with at z > 6 provides a unique laboratory to the study of the mass assembly and galaxy formation around the most massive black holes at cosmic dawn. It raises further challenges to the black hole/galaxy co-evolution in the epoch of cosmic reionization because the black hole needs to grow much faster than the host galaxy.